PREVALENCE OF ANXIETY AND STRESS AND ASSOCIATED FACTORS AMONG HEALTHCARE WORKERS AT THAI NGUYEN NATIONAL HOSPITAL IN 2026 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the prevalence of anxiety and stress and to identify associated factors among healthcare workers at Thai Nguyen National Hospital in 2026.Methods: A cross-sectional descriptive study was conducted from December 2025 to July 2026 among 400 healthcare workers working at Thai Nguyen National Hospital. Participants were selected using a multistage random sampling method. Data were collected using a structured questionnaire and the DASS-42 to assess anxiety and stress. Data were analyzed using SPSS software, applying descriptive statistics, Chi-square tests, and multivariable logistic regression analysis.Results: The prevalence of anxiety among healthcare workers was 17.2%, including mild, moderate, severe, and extremely severe anxiety at 8.5%, 5%, 2.2%, and 1.5%, respectively. The prevalence of stress was 33.7%, with mild, moderate, severe, and extremely severe stress accounting for 11.5%, 10%, 8.2%, and 4%, respectively. Multivariable logistic regression analysis showed that anxiety was independently associated with chronic disease status (OR = 8.657) and poor relationships with colleagues (OR = 6.559). Stress was associated with age ≤ 35 years, being single, having a chronic disease, working beyond regular office hours, and poor relationships with colleagues.Conclusion: The prevalence of anxiety and stress among healthcare workers at Thai Nguyen National Hospital remains considerable, particularly stress. Screening programs, psychological support interventions, and workplace environment improvements should be implemented to promote the mental well-being of healthcare workers.
Keywords: Healthcare workers, prevalence of anxiety, stress, Thai Nguyen National Hospital.